Cyclodextrin‐Based Polymer‐Assisted Ru Nanoparticles for the Aqueous Hydrogenation of Biomass‐Derived Platform Molecules. Issue 32 (14th November 2017) - Chen, Manyu; Dong, Qifeng; Ni, Wenxiu; Zhao, Xiuge; Gu, Qingwen; Tang, Guoping; Li, Difan; Ma, Wenbao; Hou, Zhenshan
Abstract: A green water‐soluble cyclodextrin polymer has been prepared through cross‐linking of β‐cyclodextrin (β‐CD) and polyethylene glycol diglycidyl ether (PEGDE). The as‐synthesized co‐polymer (PEG‐CD) showed an excellent ability to stabilize and constrain the size of Ru‐Nanoparticles in aqueous phase, as compared with other polymer stabilizer used in this work such as polyvinyl pyrrolidone (PVP−K30) and polyethylene glycol diglycidyl ether (PEGDE). The co‐ploymer PEG‐CD‐stabilizied Ru NPs have been found to be a highly efficient catalyst in the aqueous hydrogenation of levulinic acid into γ‐valerolactone under mild reaction condition. This catalyst system can be easily extended to the selective hydrogenation of other lignocellulose‐derived platform molecule including 5‐hydroxymethylfurfural, furfural, phenol, 2‐methoxy‐4‐methyl phenol and 2‐methoxy‐4‐ethyl phenol, etc. The further characterization analysis indicated that the small‐sized and highly dispersed Ru NPs (1.2‐2.0 nm) embedded in co‐ploymer PEG‐CD matrix were highly stable for the consecutive catalytic recycles. Additionally, the inclusion interaction of substrate molecules and β‐CD units within polymer matrix played a crucial role in the enhancement of catalytic performance. Abstract : A green water‐soluble cyclodextrin polymer has been prepared through cross‐linking of β‐cyclodextrin and polyethylene glycol diglycidyl ether, which was able to stabilize Ru NPs effictively. The as‐synthesized Ru NPs with small‐size (1.2‐2.0 nm) were highly efficient catalysts in the aqueous hydrogenation of levulinic acid and other biomass‐derived platform molecules. The further characterization analysis indicated that the Ru NPs were well dispersed in the aqueous media even after the consecutive catalytic recycles.